A Holistic Approach to Utilize Mycorrhizae for Improving Soil Health and Enhancing Yield of Wheat in Bangladesh (Journal of Science and Technology Research, 2022)
Arbuscular mycorrhizal fungi (AMF) species may have positive impacts on wheat productivity through translocation of nutrients within wheat plant tissue. To quantify effect of mycorrhizae species on wheat plant productivity, two experiments were conducted in this study. One preliminary seedlings growth experiment was conducted in sand culture to reckon exact mycorrhizae effect on wheat seedlings growth response and changes in sand properties due to mycorrhizae inoculation. Another pot experiment was conducted to quantify wheat productivity, nutrient content within wheat plant tissue and changes in soil physiochemical characteristics due to four mycorrhizae species amendment. Result showed that wheat seedling responded better due to mycorrhizae inoculation. Mycorrhizae inoculation also improves nutrient content within wheat seedlings tissue and store carbon in sand. Finding also showed that mycorrhizae species inoculation increased growth and yield of wheat as well as phosphorus accumulation within wheat grain. Both experiments showed that mycorrhizae species inoculums store carbon in soil and within wheat plant tissue.J. of Sci. and Tech. Res. 3(1): 01-10, 2021